Analisis Prosedur Rekonsiliasi Bank pada Badan Keuangan dan Aset Daerah Kota Medan - Nasution, Annio Indah Lestari; Telambanua, Berlian; Anggraini, Nur Marliana; Rao, Rofiqoh Hannum (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study aims to analyze bank reconciliation procedures for regional financial institutions and assets in the city of Medan and researchers want to know the procedures for the bank reconciliation system for the Medan City Regional Financial and Asset Management Agency (BKAD). The method used in this research is a qualitative descriptive research method and in practice this research collects data and looks for references from journals and manuals. The data analysis technique used in this study was data obtained qualitatively and data collection in this research method also carried out field observations, and direct interviews with employees who were in the Regional Financial and Asset Management Office of the Medan Mayor's Office. From the results of data analysis, conclusions can be drawn and the results of the research found that the bank reconciliation procedure in the BKAD treasury sector in the city of Medan still has deficiencies, namely the checking account submitted is still in the form of paper, so the author analyzes the excessive use of paper. In addition, the bank data reconciliation process still uses a manual process that takes a long time. Keywords : procedure, reconciliation, bank data.